'Driving-as-Event': re-thinking the car journey. Issue 4 (4th July 2017) - Pearce, Lynne
Abstract: This article explores the possibility of 'measuring' the individual car journey in terms of the quality of the cognitive distance travelled by the car's occupants. Literary texts constitute an invaluable resource in this regard since their focus on the interiority of the driving experience is of great help in the theorisation of what I refer to here as 'automotive consciousness'. In the discussion that follows, I propose that each and every car journey may be thought of as a unique and non-reproducible event in the lives of the drivers and passengers concerned on account of the variable psychological and situational factors involved.